Efektivitas Penanaman Mangrove oleh KKN dalam Meningkatkan Ketahanan Ekosistem Pesisir Desa Bacu - Fadil, Fadil Astriadi Sofyan; Tanti, Tanti Sugita; Justiana Rahmasari; Elis; Andika Akbar; Juheria; Bob Ical; Asma Anti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Coastal ecosystem degradation caused by abrasion and human activities has become a serious issue in many coastal areas, including Bacu Village. Mangroves play a crucial role in protecting shorelines, sequestering carbon, and providing habitats for marine organisms. A community service program through the Kuliah Kerja Nyata (KKN) initiative was implemented as a conservation effort as well as community empowerment. The methods consisted of three main stages: seedling preparation, land preparation, and the planting of Rhizophora mucronata and Rhizophora stylosa mangroves. The results showed the successful planting of 2,000 seedlings with a survival rate of approximately 85% after one month. Furthermore, community participation, particularly among fishermen and youth groups, increased significantly, reflecting a shift from passive to more active involvement in coastal environmental protection. This activity proved to deliver ecological benefits by reducing abrasion rates and socio-economic benefits through potential mangrove-based ecotourism. Therefore, the mangrove planting program in Bacu Village is considered effective in strengthening coastal ecosystem resilience and enhancing community awareness of environmental conservation.